Penerapan Sanksi Terhadap Importir Barang Yang Tidak Baru Di Kabupaten Indragiri Hilir Berdasarkan Undang-Undang Nomor 07 Tahun 2014 Tentang Perdagangan - Muhammad Arif; Ardiansyah; Sudi Fahmi (UIR Law Review, 2022)
Trade is the main engine for the development of the national economy. Trading activities increase production, increase exports which increase foreign exchange, create jobs, distribute income, and strengthen the competitiveness of domestic products. The purpose of this study is to analyze how sanctions are applied to importers of non-new goods in Indragiri Hilir district based on Law Number 07 of 2014 concerning trade, and to analyze constraints and efforts in applying sanctions to importers of non-new goods in the district. Indragiri Hilir. The results in this study are imported used clothing is an item that is considered illegal in Indonesia. The meaning here is illegal, namely something that is not in accordance with applicable laws or regulations. What are the obstacles, namely Non-Juridical and Juridical Constraints, in the Non-Juridical constraints "the smuggling of used clothes in Inhil is a very serious problem besides causing losses to state finances it also has an impact on the health of users of used clothes because it is indicated there are several bacteria that can endanger human health. Seeing these problems, of course there are efforts made by local stakeholders, namely from non-juridical efforts of stakeholders to work together synergistically. In juridical constraints, it is found that efforts of stakeholders provide advice and input to legislators so that incidents in the field can be resolved by basic rules that strong. Keywords: Sanctions, Goods Importers, Trade.